Nutritional Assessment of Dietary Bt and Cp4EPSPS Proteins on the Serum Biochemical Changes of Rabbits at Different Developmental Stages - Salisu, Ibrahim B.; Shahid, Ahmad A.; Ali, Qasim; Rao, Abdul Q.; Husnain, Tayyab (Frontiers in Nutrition, 2018)
In recent years, the influence of genetically modified (GM) cotton expressing different types of Bt and EPSPS genes has been attested in term of reduced application of pesticides and insecticides coupled with improved cotton production. Although the cultivation of GM cotton has been authorized by the regulatory authorities of various countries in the world, based on the biosafety studies reported by most of the GM cotton producers, yet the information on its safe use are inadequate. In order to support the issues on food safety, it is therefore mandatory to conduct further safety assessment studies on GM cotton for each independent transgenic event on basis of case assessment rule. In the present study, the effects of different doses of dietary GM cotton seed expressing Bt and EPSPS genes were studied on the level of serum biochemical in albino rabbits (Oryctolagus caniculus). The rabbits were fed a diet containing different levels of GM cotton seeds (i.e. 20% w/w, 30% w/w and 40% w/w) respectively mixed with standard diet for 180 days. During the course of the study, various serum enzymes, electrolytes, proteins, glucose and serum total cholesterol were examined at specific time intervals (0, 45, 90, 135 and 180) days. The results showed non-significant (P>0.05) dose dependent effects in most of the evaluated serum biochemical parameters. Although, the results in some of the serum biochemistry were significantly different (P<0.05) among the groups, however, they were not biologically significant, since all the differences were within the normal physiological range. These results thus, suggested that the GM cotton seed meal could be considered as safe as other conventional feed ingredients. The experimental evidence for the safe usage of GM cotton was highlighted in this study.